Diagnóstico patológico y propuesta de intervención de los cimientos y de los muros de contención de derrames de dos tanques de almacenamiento de ácido sulfúrico para usos industriales - Dikdan, M.Y.; de Corrales, R. M.; Avon, D. (Revista ALCONPAT, 2013)
In an industrial facility, several failure symptoms were found on walls, floor slab, and foundations of concrete tanks designed to contain eventual spilling from two metallic containers of sulfur acid (one at 11% concentration, and the other at 98%). Loss of connection between lateral walls and floor slab was observed. Interior wall areas and foundations of tanks were covered with epoxy material which was mostly peeled off. By extraction of concrete nucleus samples, the following parameters were determined: carbonation, porosity, sulfate penetration, and compressive strength. Reinforcing bars were tested for: concrete cover thickness, diameter, potential measurements (Cu/SO4Cu), and corrosion rate. Remaining structural capacity of concrete walls was calculated, concluding that the structure is severely affected by sulfur acid. Two actions are suggested: a provisional one by constructing big reinforced concrete cubes around the tank to make it stable; the other, a final solution, replacing the sulfur acid containers and the concrete tank for possible sulfur infiltration to the ground underneath them. Key words: Tanks, Sulfur acid, disaggregation, corrosion, walls